2022
DOI: 10.1177/07334648221119464
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Changes in Depression/Anxiety Symptoms and Fall Worry Among Community-Dwelling Older Adults

Abstract: Using the 2019 and 2020 National Health and Aging Trend Study, we examined the association between fall worry and changes in depression/anxiety symptoms among community-dwelling older adults age 70+ ( N = 3333). Past-month fall worry in 2020 included any fall worry (30.9%) and activity-limiting fall worry (34.0% of those with any fall worry). Changes in depression/anxiety symptoms referred to an increase or decrease in the Patient Health Questionnaire-4 symptom categories between 2019 and 2020. Those with fall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Frailty may predispose to worrying about falling and experiencing falling. Worrying about falling has been associated with depressive symptoms in aging adults [48]. In this sample (N=3,333 greater than 70-years-old), those with fall worry had more moderate/severe depressive symptoms in 2019 and an increase in fall worrying by 2020.…”
Section: Physical Healthmentioning
confidence: 77%
“…Frailty may predispose to worrying about falling and experiencing falling. Worrying about falling has been associated with depressive symptoms in aging adults [48]. In this sample (N=3,333 greater than 70-years-old), those with fall worry had more moderate/severe depressive symptoms in 2019 and an increase in fall worrying by 2020.…”
Section: Physical Healthmentioning
confidence: 77%
“…These findings suggest that a single fall over the 3 years could have been an accident (e.g., due to environmental hazards) and did not necessarily indicate health disadvantages among those who fell, while recurrent falls were likely indicators of significant health disadvantages. Previous research has shown reciprocal relationships among frailty, activity limitation, fall worry, depression/ anxiety, and falls (Choi et al, 2020(Choi et al, , 2022de Souza et al, 2022;Iaboni & Flint, 2013;Makino et al, 2021;Merchant et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies have mainly examined the associations between pain in the lower extremity, hip, and back, and fall worry for older adults ( 43 , 57–59 ). We found that pain in the lower body (knee, foot, and leg) and the upper body (hand, wrist, shoulder, neck, and stomach) was associated with activity-limiting fall worry for older people with CI after adjusting covariates.…”
Section: Discussionmentioning
confidence: 99%
“…“Falling down” was defined as any fall, slip, or trip, which resulted in a loss of balance and landing on the floor or ground or at a lower level. Responses to these 2 items were used to generate a 3-level ordinal variable, “no fall worry,” “nonactivity-limiting fall worry,” and “activity-limiting fall worry.” This ordinal variable of fall worry has been used as a dependent variable in previous studies of older people with and without CI ( 11 , 43 ).…”
Section: Methodsmentioning
confidence: 99%